Persepsi Pengunjung Terhadap Display Lahan Pekarangan Teknologi Pertanian Di Taman Agro Inovasi BPTP Jawa Tengah - Komalawati Komalawati; Sarjana Sarjana (Jurnal Riset Agribisnis dan Peternakan, 2019)
The Central Java Agro Innovation Center for Agricultural Technology Research (BPTP) was built as a means of promotion and demonstration of agricultural land yard technology produced by the Agency for Agricultural Research and Development. Agricultural technology includes conventional direct on-land cultivation, hydroponic cultivation, aquaponic cultivation, horticulture, and crop cultivation in a limited media container. The purpose of this paper is to examine visitors' perceptions of technology display in Central Java AIAT Agro Innovation Park. Data obtained through interviews with visitors and analyzed using a Likert scale. The results of the study show that visitors have a very positive perception of agricultural technology found in the Agro Innovation Park because it suits the needs of the community and can increase household income. However, visitors hope that the agricultural technology display can be better and widely introduced to the public.